Reduced airborne transmission of SARS-CoV-2 BA.1 Omicron virus in Syrian hamsters - Boon, Adrianus C. M.; Darling, Tamarand L.; Halfmann, Peter J.; Franks, John; Webby, Richard J.; Barouch, Dan H.; Port, Julia R.; Munster, Vincent J.; Diamond, Michael S.; Kawaoka, Yoshihiro (PLOS Pathogens, 2022)
JRP and VJM are supported by the Intramural Research Program of the National Institute of Allergy and Infectious Diseases (NIAID), National Institutes of Health (NIH). The authors report no other conflict of interest. Since the start of the COVID-19 pandemic, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused hundreds of millions of infections worldwide with more than 6.5 million confirmed deaths. Transmission of SARS-CoV-2 can be established by detection of viral RNA, RNA replication intermediates, viable infectious virus, or seroconversion, with the latter two metrics being the most stringent. Since January 2021, the National Institutes of Health SARS-CoV-2 Assessment of Variant Evolution (SAVE) initiative has evaluated the transmission potential of SARS-CoV-2 variants in Syrian hamsters [16]. [...]it is possible that the changes in the spike protein of Omicron affect and reduce stability of the virus in the infected hosts.